FLIPPED CLASSROOM: ALTERNATIVE OF THE MODEL OF LEARNING TO IMPROVE STUDENT LEARNING OUTCOMES IN K-10 - Maria Paristiowati; Ucu Cahyana; Annisa Nur Fitria (Program Pascasarjana Universitas Negeri Jakarta, 2017)
This study aimed to determine the effect of applying the flipped classroom model to students’ learning outcomes in oxidation-reduction reactions. It was conducted in SMAN 47 Jakarta. Research method is quasi-experimental with nonequivalent control group design. The sample consisted of 72 students were taken with purposive sampling. Independent variables are the flipped classroom model and direct instructional. Chemistry learning outcome became a dependent variable. The flipped classroom model is invers of the traditional learning model. Students learn the instructional material at home through videos and discussions in class. Analysis of the requirement’s test showed that the data were normally distributed and had homogeneous variances. Hypothesis testing showed different results in a significant level of 0.05. The differences of average value between pretest and posttest of the experimental group is 12.50. While the differences in the control group was 7.17. It can be concluded that the difference of average value between pretest and posttest of the experimental group is higher than the control group. The flipped classroom model can improve students’ learning outcomes in the oxidation-reduction reaction.